Pembelajaran Pendidikan Agama Islam Bagi Peserta Dauroh Shoifiyah Darul Musthafa, Tarim, Yaman - Irfan, Ahmad; Lubis, Adlan Fauzi; Setiady, Dicky; Muhamad, Muhamad (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
The closeness between Indonesian scholars (ulama) and scholars from Hadhramaut, Yemen, is undeniable, as we have known through various literature and the existence of habaib (Islamic scholars) in Indonesia. The Dauroh Shoifiyyah Tarim Hadhramaut program in 2023 was conducted in Darul Musthafa and Daruzzahra, Hadhramaut. This research aims to describe and explain the learning program, the supporting factors, the hindering factors, and the impacts of the Dauroh Shoifiyyah program in 2023. This research was conducted using a qualitative method, specifically phenomenological research. The learning program of Dauroh Shoifiyyah covers topics such as creed (aqidah), jurisprudence (fiqih), interpretation of the Quran (tafsir), traditions of the Prophet (hadis), the biography of the Prophet (sirah nabawiyah), transactions (muamalah), Islamic mysticism (tasawuf), preaching (dakwah), and retracing the steps of past scholars (napak tilas ulama-ulama terdahulu). Supporting factors for this program can be found in the services provided by the Dauroh committee, while hindering factors include health issues and language differences. The impacts generated include serving as role models for teachers emulated by the participants and the cultivation of the habit of remembrance (dhikr) and sending blessings upon the Prophet (bershalawat) by the participants. Keywords: Learning, Dauroh, Habib Omar, Tarim